Barriers and facilitators to hepatitis C screening and treatment for people with lived experience of homelessness: A mixed‐methods systematic review. (3rd December 2021) - Paisi, Martha; Crombag, Neeltje; Burns, Lorna; Bogaerts, Annick; Withers, Lyndsey; Bates, Laura; Crowley, Daniel; Witton, Robert; Shawe, Jill
Abstract: Background: People experiencing homelessness have an increased risk of hepatitis C virus (HCV) infection, with rates higher than the general population. However, their access to HCV diagnosis is limited and treatment uptake is low. Objectives: To identify and describe the barriers and facilitators for HCV screening and treatment for adults with lived experience of homelessness in highly developed countries. Methods: Bibliographic databases (Embase, MEDLINE, CINAHL and SocINDEX) and grey literature (Google, EThOS, the Health Foundation, Social Care Online, the World Health Organisation, Shelter, Crisis and Pathway) were searched. Two reviewers independently screened and appraised all studies. The Critical Appraisal Skills Programme tool and the Joanna Briggs Institute checklist were used. The analysis involved a three‐stage process: coding, theme generation and theme mapping under Penchansky and Thomas's modified access model. Results: Twelve papers/reports were included in the review. Several interacting factors influence access of people with lived experience of homelessness to HCV testing and treatment. Some mirror those identified for the general population. The precarious conditions associated with the lived experience of homelessness along with the rigidity of hospital settings and lack of awareness emerged as dominant barriers. Flexibility, outreach, effective communication, tailoring and integration of services were found to be important facilitators. Evidence from Black, Asian and minority ethnic groups is limited. Conclusions: People experiencing homelessness face multiple barriers in accessing and completing HCV treatment, relating to both their lived experience and characteristics of health systems. Although some barriers are readily amenable to change, others are more difficult to modify. The facilitators identified could inform future targeted measures to improve HCV diagnosis and treatment for people experiencing homelessness. Research is warranted into successful models to promote screening, diagnosis and treatment. Patient or Public Contribution: Our team includes a peer advocate, a hepatology nurse and a community volunteer, all with significant experience in promoting and engaging in HCV care and outreach for people experiencing homelessness. They contributed to the protocol, interpretation and reporting of the review findings.